а)2sin²x-3sinx-2=0
Замена sinx=t
2t²-3t-2=0
D=3²+4×2×2=25
t₁= 3+√D÷4=3+5÷ 4=8÷4=2
t₂=3-√D÷4=3-5÷4=-2÷4=-0,5
Возвращаемся к замене
sinx=2 sinx=-0,5
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
4cos²x+4sinx-1=0
cos²x=1-sin²x
4( 1-sin²x)+4sinx-1=0
4-4sin²x+4sinx-1=0
-4sin²x+4sinx-1+4=0
-4 sin²x+4sinx+3=0 ÷(-1)
4sin²x-4sinx-3=0
Замена sinx=t
4t²-4t-3=0
D=4²+4×4×3=16+48=64
t₁=4+√D÷8= 4+8÷8=12÷8=1,5
t₂=4-√D÷8=4-8÷8= -4÷8=-0,5
Возвращаемся к замене
sinx=1,5 sinx=-1\2
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
1) 7,91:0,565=14
2)44,4:5,92=7,5
3)14-7,5=6,5
4)6,5*0,5=3,25
5) 0,2:0,004=50
6)50+3,25=53,25.
2) 4,735:0,5+14,95:1,3+2,121:0,7=24
1)4,735:0,5=9,47
2)14,95:1,3=11,5
3)2,121:0,7=3,03
4)9,47+11,5+3,03=24.
3) (0,1955+0,187):0,085=2,3955
1) 0,1955+0,187)=0,3825
2)0,3825:0,085=2,3955.
4) (86,9+667,6):(37,1+13,2)=15
1)86,9+667,6=754,5
2)37,1+13,2=50,3
3)754,5:50,3=15
5) (0,008+0,992)*(5*0,6-1,4)=1,6
1)0,008+0,992=1
2)5*0,6=3
3)3-1,4=1,6
4)1*1,6=1,6